DNA‐Origami‐Templated Silica Growth by Sol–Gel Chemistry. Issue 3 (11th December 2018) - Nguyen, Linh; Döblinger, Markus; Liedl, Tim; Heuer‐Jungemann, Amelie
Abstract: Improving the stability of DNA origami structures with respect to thermal, chemical, and mechanical demands will be essential to fully explore the real‐life applicability of DNA nanotechnology. Here we present a strategy to increase the mechanical resilience of individual DNA origami objects and 3D DNA origami crystals in solution as well as in the dry state. By encapsulating DNA origami in a protective silica shell using sol–gel chemistry, all the objects maintain their structural integrity. This allowed for a detailed structural analysis of the crystals in a dry state, thereby revealing their true 3D shape without lattice deformation and drying‐induced collapse. Analysis by energy‐dispersive X‐ray spectroscopy showed a uniform silica coating whose thickness could be controlled through the precursor concentrations and reaction time. This strategy thus facilitates shape‐controlled bottom‐up synthesis of designable biomimetic silica structures through transcription from DNA origami. Abstract : Coating concepts : The resilience of DNA origami objects and crystals has been increased through encapsulation in silica. Energy‐dispersive X‐ray spectroscopy showed a uniform silica coating, whose thickness could be controlled through the reactant concentrations and reaction time. This biomimetic approach is an important step toward shape‐controlled bottom‐up synthesis.